17-3(2x-7)=7x-3(2x-1)equation

Simple and best practice solution for 17-3(2x-7)=7x-3(2x-1)equation equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-3(2x-7)=7x-3(2x-1)equation equation:


Simplifying
17 + -3(2x + -7) = 7x + -3(2x + -1) * equation

Reorder the terms:
17 + -3(-7 + 2x) = 7x + -3(2x + -1) * equation
17 + (-7 * -3 + 2x * -3) = 7x + -3(2x + -1) * equation
17 + (21 + -6x) = 7x + -3(2x + -1) * equation

Combine like terms: 17 + 21 = 38
38 + -6x = 7x + -3(2x + -1) * equation

Reorder the terms:
38 + -6x = 7x + -3(-1 + 2x) * equation

Reorder the terms for easier multiplication:
38 + -6x = 7x + -3aeinoqtu(-1 + 2x)
38 + -6x = 7x + (-1 * -3aeinoqtu + 2x * -3aeinoqtu)
38 + -6x = 7x + (3aeinoqtu + -6aeinoqtux)

Reorder the terms:
38 + -6x = 3aeinoqtu + -6aeinoqtux + 7x

Solving
38 + -6x = 3aeinoqtu + -6aeinoqtux + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6aeinoqtux' to each side of the equation.
38 + 6aeinoqtux + -6x = 3aeinoqtu + -6aeinoqtux + 6aeinoqtux + 7x

Combine like terms: -6aeinoqtux + 6aeinoqtux = 0
38 + 6aeinoqtux + -6x = 3aeinoqtu + 0 + 7x
38 + 6aeinoqtux + -6x = 3aeinoqtu + 7x

Add '-7x' to each side of the equation.
38 + 6aeinoqtux + -6x + -7x = 3aeinoqtu + 7x + -7x

Combine like terms: -6x + -7x = -13x
38 + 6aeinoqtux + -13x = 3aeinoqtu + 7x + -7x

Combine like terms: 7x + -7x = 0
38 + 6aeinoqtux + -13x = 3aeinoqtu + 0
38 + 6aeinoqtux + -13x = 3aeinoqtu

Add '-38' to each side of the equation.
38 + 6aeinoqtux + -38 + -13x = -38 + 3aeinoqtu

Reorder the terms:
38 + -38 + 6aeinoqtux + -13x = -38 + 3aeinoqtu

Combine like terms: 38 + -38 = 0
0 + 6aeinoqtux + -13x = -38 + 3aeinoqtu
6aeinoqtux + -13x = -38 + 3aeinoqtu

Reorder the terms:
38 + -3aeinoqtu + 6aeinoqtux + -13x = -38 + 3aeinoqtu + 38 + -3aeinoqtu

Reorder the terms:
38 + -3aeinoqtu + 6aeinoqtux + -13x = -38 + 38 + 3aeinoqtu + -3aeinoqtu

Combine like terms: -38 + 38 = 0
38 + -3aeinoqtu + 6aeinoqtux + -13x = 0 + 3aeinoqtu + -3aeinoqtu
38 + -3aeinoqtu + 6aeinoqtux + -13x = 3aeinoqtu + -3aeinoqtu

Combine like terms: 3aeinoqtu + -3aeinoqtu = 0
38 + -3aeinoqtu + 6aeinoqtux + -13x = 0

The solution to this equation could not be determined.

See similar equations:

| 4*x^2*(x-1)=17*x^2-25 | | 16=-11a+2a | | 2(x-1)(x+1)=8 | | x^2*(x^2-1)=17*x^2-25 | | x^2*(x-1)=17*x^2-25 | | 6p-9=-4p+7 | | 2.01x+0.06=17.04 | | 2.01+0.06=17.04 | | 121/5=x | | 7=9y-4y-3 | | https://vk.com/id411503749 | | 6tanx+1=0 | | 2(x-6)=-3(x-5) | | 5C+12=7C+10.98 | | 36x^2+12x-7=0 | | 4.9X-4.5=41.56 | | 21/4x1/4 | | 437.5-0.5x^2=0.2x^2 | | (3x+9)=(3x-1.5) | | -5.81=4.87Z-5.81 | | 8.6T+7.96=-27.30 | | (5u-3)(2-u)=0 | | (x^3)-6x+5=0 | | -3.9X=-246.09 | | 2(x-1)(x+1)= | | x^2-(x-1)=y | | 7.31=17Z | | f(x)=x^4-3x^3-2x^2 | | X=20log(4) | | 5x+2(x-3)=-2(c-1) | | x^4+2x^3-7x^2+3=0 | | -6=18/p |

Equations solver categories